A Growing Stem Inhibits Bud Outgrowth – The Overlooked Theory of Apical Dominance - Kebrom, Tesfamichael H. (Frontiers in Plant Science, 2017)
Three theories of apical dominance, direct, diversion and indirect, were proposed in the 1930s to explain how auxin synthesized in the shoot apex might inhibit axillary bud outgrowth, and thus shoot branching. The direct and diversion theories of apical dominance have been investigated in detail, and they are replaced with the current auxin transport canalization and second messenger theories, respectively. These two current theories still cannot entirely explain the phenomenon of apical dominance. Although there is ample evidence that the inhibition of bud outgrowth by auxin from the shoot apex is linked to stem elongation and highly branched auxin biosynthesis or signaling mutants are dwarf, the third theory proposed in the 1930s, the indirect theory, that explains apical dominance as auxin-induced stem growth indirectly inhibits bud outgrowth has been overlooked. The indirect theory did not propose how a growing stem might inhibit bud outgrowth. Recent discoveries indicate bud dormancy (syn. quiescence, paradormancy) in response to intrinsic and environmental factors in diverse species is linked to enhanced growth of the main shoot and reduced sugar level in the buds. Since a growing stem is a strong sink for sugars, and sugar is indispensable for shoot branching, the indirect theory of apical dominance might now be explained as auxin-induced stem growth inhibits bud outgrowth by diverting sugars away from buds. Detailed study of the indirect theory and the effect of source-sink status on dormancy and out growth of axillary buds will advance our knowledge of apical dominance and shoot branching in plants.